Առանձարի ստեղծագործությունը և ռեալիզմի հարցերը - Մախմուրյան, Ա. Հ. (Հայկական ԽՍՀ գիտությունների ակադեմիա)
В развитии западноармянской реалистической сатиры начала XX века особенно значительна роль Арандзара (Мисака Гуюмчяна). Некоторые его новеллы отражают эстетические воззрения автора,сама же сатира выявляет проблемы, имеющие идеологическое значение для литературы и печати. The role of Arandzar (Misak Guyumjian) in the development of the West Armenian realistic satire at the beginning of the 20th century has been considerable. A number of his short stories reflect the author's artistic views, while his satire reveals fundamental questions, which bear ideological significance for literature and the press.
Keywords: Literature; Language and Literature